PERCEPTIONS OF UNETHICAL PRACTICES IN INSURANCE INDUSTRY - Mohd. Zabid Abdul Rashid; Mohd. Zabid Abdul Rashid; Kamaruddin Shariff (Asian Academy of Management Journal, 1996)
Currently, the issue of ethics has gained increasing prominence in management studies. It has received much attention among academics and practitioners. Ethics, which is seen as a theoretical luxury indulged by firms in the Western countries are now given greater attention by business leaders in Asia (McGrath, 1993) In Malaysia, the issue of ethics has gained the attention of public policy decision-makers and top managers in large organisations. The increasing number of incidences in white collar crimes' has also resulted in the Prime Minister directing the local universities to conduct appropriate courses in business ethics. In fact, one of the key aspirations of the Malaysian Vision 2020 is to ensure the prevalence of high moral values among the populace.